Component Hybridization in Thin Granulated C60−Cu Nanocomposite Films - Dmytrenko, O.P.; Pavlenko, O.L.; Kulish, M.P.; Zabolotnyi, M.A.; Kornienko, M.E.; Brusentsov, V.A.; Rybii, V.M.; Shpilevskyi, E.M. (Ukrainian Journal of Physics, 2022)
Thin granulated films of C60–Cu nanocomposite with the Cu contents of 80, 34, and 8 at.% were fabricated with the use of the vacuum codeposition method. The films were annealed at a temperature of 473 K for 10, 20, and 30 h in vacuum. Films with lower Cu contents demonstrated a drastic relative intensity decrease and a broadening of the Ag(2) dipole-active vibrational band in the Raman spectrum, which is sensitive to the charge transfer from metal atoms to C60 molecules. Further annealing was accompanied not only by a decrease of this band intensity, but also by an intensity increase and a broadening of the Hg(8) vibrational mode band. Moreover, annealing gave rise to the growth of the triplet radiation emission intensity. Similar processes, but with some delay, also occurred in a granular film with a higher copper content. The transformation of Raman and photoluminescence spectra evidenced the polymerization and the destruction of C60 molecules owing to the diffusion of copper atoms into C60 crystallites, followed by the chemical interaction between those two components due to the charge transfer from metal atoms to fullerenes.